Acute Effect of Transcutaneous Electroacupuncture on Globus Pharyngeus: A Randomized, Single-Blind, Crossover Trial - Zhou, Wencong; Deng, Qi; Jia, Lin; Zhao, Hanbing; Yang, Meng; Dou, Guoyuan; He, Zijian; Guo, Wanwei (Frontiers in Medicine, 2020)
Background: Acupuncture points are commonly used by Traditional Chinese Medicine to treat throat discomfort. Transcutaneous electroacupuncture is a new therapy combining transcutaneous electrical nerve stimulation with meridian theory. The efficacy and mechanism of Transcutaneous electroacupuncture for globus pharyngeus has not been reported. Methods: In the study, 80 patients of globus were divided into eight groups. Before and after treatment, each patient was asked to finish some tests and blood samples were taken. Then compare the differences before and after treatment. Results: D-values of Glasgow Edinburgh Throat Scale and visual analogue scale in stimulating at CV22/LU11 were significantly higher than those of sham- stimulating. Heart rate variability, substance P and neuropeptide Y were showed significant difference in LU11 stimulating compared with other acupuncture points. Conclusion: Stimulating at CV22/LU11 significantly improves symptoms of globus. The results indicated that symptoms may be improved by stimulating the parasympathetic nervous system, and secreting substance P and neuropeptide Y when stimulating at LU11. For CV22, it may improve symptoms by direct action on the throat. Stimulating at CV22/LU11 may be a potential therapy for treating globus.